Understanding and profiting from intellectual property in international business : strategies across borders - Yang, Deli, 1964- (Palgrave Macmillan, 2021)
This book covers cross-border strategies to understand and profit from intellectual property. It starts with a basic overview of IP before focusing specifically on international business contexts. The book then explores factors that affect IP-related business activities in different countries. Next, follows a discussion of the importance of managing IP valuation, people, and products, which leads into an examination of strategies for obtaining value from IP-related activities, including licensing. This edition updates the contents and adds new contemporary cases, such as internet-based crimes and trademarked sport brands. Readers will gain an understanding of the significance of IP to corporate success in the increasingly globalized world. With updated knowledge on deriving value from IP, this book will provide insights for practitioners to deal with cross-border issues of IP, and for scholars across disciplines to advance studies of cross-border issues and conflicts in IP.